Would It Be The Same? Measuring Mental Health Status in Conventional Vs. Digital Way - Octaviani Indrasari Ranakusuma; Ummi Azizah Rachmawati; Nova Eka Diana; Farhan A. Darmawanto; Eresha Tirtan; Fido O. Sucipto; Rifki A. Hasibullah; Dio Mafazi (Applied Quantitative Analysis, 2022)
Adolescents are facing challenges which puts them in risks of having emotional problems. Early detection of those who are at risk developing mental health problem is required to prevent them from worsening and thus need advanced and costly clinical treatments. However, students have limited access to mental health services due to lack of knowledge of mental health. Social stigmatization has also been a barrier to access the services. Numbers of mental health digital application has been developed. There are controversies whether digital application measures one’s mental health status.  The study compared scores of depression, anxiety, and stress subscales of DASS-42 (Depression, Anxiety, and Stress Scale 42 items) obtained by paper-and-pencil (conventional) questionnaire and by GALAW V.2 android-based application. It is hypothesized that insignificant scores differences between the modes of measurement demonstrated that the digital application could replace the conventional questionnaire. Thirty high school students (N=30) participated in the study. The conventional measurement (paper-and-pencil questionnaire) was conducted first. After 60 minutes break, the students completed the measurement provided digitally in the application. It showed that the mean of anxiety subscale did not significantly differ (t=1.22; p=.23) whether using digital or conventional mode. On the other hand, the paired t-test demonstrated significant mean differences in the depression (t=3.63, p=.00) and stress (t=2.32, p=.03) subscales of DASS-42. Finally, the result of the study cannot be generalized due to the small number of participants. It is advised to have more participants to represent the population. Other measurements such as the Beck Depression Inventory (BDI) and The State-Trait Anxiety Inventory (STAI) were highly recommended for validity purpose